Pengaruh Fraud Risk Factors dengan pendekatan pentagon terhadap kecurangan laporan keuangan - Sasana, Lodang Prananta Widya; Abidin, Jaenal; Indrawan, I Gede Adi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of fraud risk factors based on the fraud pentagon approach on financial statement fraud in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX). The fraud pentagon approach is employed as it provides a more comprehensive analytical framework for identifying the potential occurrence of financial statement fraud. The research sample consists of 14 SOEs listed on the IDX during the 2018–2022 period, selected using a purposive sampling technique. This study utilizes secondary data obtained from companies’ annual reports and financial statements. Panel data regression analysis is applied using EViews 12 as the analytical tool. The independent variables examined include financial stability, ineffective monitoring, government ownership, auditor turnover, director turnover, and managerial ownership, while financial statement fraud serves as the dependent variable. One of the key contributions of this study is the use of government ownership as a proxy for the rationalization element within the fraud pentagon framework, which has been rarely applied in prior studies. The results indicate that, partially, financial stability, government ownership, auditor turnover, and director turnover do not have a significant effect on financial statement fraud. In contrast, ineffective monitoring and managerial ownership are found to have a significant effect. Simultaneously, all independent variables collectively influence financial statement fraud. These findings are expected to contribute theoretically to the development of fraud pentagon literature and provide practical implications for strengthening corporate governance in SOEs.